Cardiorespiratory capacity and body composition in girls and adolescents practitioners of rhythmic gymnastics - Montosa, I.; Vernetta, M.; López-Bedoya, J. (Archivos de medicina del deporte, 2018)
Introduction: Aerobic capacity is one of the qualities to be developed in rhythmic gymnastics sport which requires huge physical and technical demands, with high loads of training.